About the Conference (IOP conference series. Materials Science and Engineering, 2019)
International Conference on Frontiers in Material and Smart Systems Technologies allows the designers to build a specific system out of components which is able to obtain the information from the surroundings, to process it electronically, to communicate signals and data and to give enabled feedback signal to the ambience. "A system or material which has built-in intrinsic sensor(s), actuator(s) and control mechanism(s) whereby it is capable of sensing a stimulus, responding to it in a predetermined manner and extent, in a short/appropriate time, and reverting to its original state as soon as the stimulus is removed". Smart systems are a network of physical objects or things that are embedded with electronics, software, sensors, and network connectivity - which enable the object to collect and exchange data. Rapid proliferation of IoT is driving the intelligence in things used daily in homes, workplaces and industry. The IoT devices typically communicate via radio frequency (RF), such as WiFi, Bluetooth and other communication networks. Smart systems and automation are ambiguous terms used in reference to a wide range of solutions for controlling, monitoring and automating functions in the home and industries. Smart devices that only can be controlled with switches, timers, sensors and remote controls are thus not included in the scope of this study in various automations covered in various applications throughout this book. Smart systems can be grouped into different categories such as energy management and climate control systems; security and access control systems; lighting, window and appliance control systems; home appliances; audio-visual and entertainment systems; and healthcare and assisted living systems. The whole system is subject to the trend of today's world: miniaturization, networking capability, energy-autonomy and reliability. Due to increasing complexity and multidisciplinary developing teams in fields of microsystems- and nanotechnology, electronics, wireless communication technologies, optics, biology, medical science, and fluidics face highest demands. There are several different communication protocols and media used for lighting control available. They have different architecture and cannot communicate between each other. Here lies the biggest challenge for us as a world. The conference will provide a platform for researchers and practitioners interested in the theory and practice of smart systems and technologies related to electrical engineering, communications, computer science and engineering, control systems, robotics, as well as interdisciplinary research and applications. Best regards, Dr. Suresh P Dr. Saravanakumar U